2012
DOI: 10.1093/cercor/bhs227
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Hub Architecture in the Human Functional Brain Network

Abstract: Functional hubs are brain regions that play a crucial role in facilitating communication among parallel, distributed brain networks. The developmental emergence and stability of hubs, however, is not well understood. The current study used measures of network topology drawn from graph theory to investigate the development of functional hubs in 99 participants, 10-20 years of age. We found that hub architecture was evident in late childhood and was stable from adolescence to early adulthood. Connectivity betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
184
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(196 citation statements)
references
References 70 publications
10
184
2
Order By: Relevance
“…Particularly noteworthy are maturational changes during adolescence, a period that coincides with heightened vulnerability to mental illness and behavioral problems (Paus et al, 2008). Understanding adolescent brain maturation is therefore critical for identifying neurodevelopmental pathways that confer risk or resilience to psychopathology (Di Martino et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Particularly noteworthy are maturational changes during adolescence, a period that coincides with heightened vulnerability to mental illness and behavioral problems (Paus et al, 2008). Understanding adolescent brain maturation is therefore critical for identifying neurodevelopmental pathways that confer risk or resilience to psychopathology (Di Martino et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) studies have found that adolescent changes in the organization of large-scale structural and functional neural networks involve the strengthening of long-range connections between distal brain regions (Fair et al, 2007(Fair et al, , 2009Kelly et al, 2009;Dosenbach et al, 2010;Hagmann et al, 2010;Dennis et al, 2013; for review, see Di Martino et al, 2014). Recent studies have suggested that these connections are supported by a collection of spatially distributed and topologically central regions-putative network hubs (Harriger et al, 2012;van den Heuvel et al, 2012;de Reus and van den Heuvel, 2013;van den Heuvel and Sporns, 2013)-and may enhance functional integration (Uddin et al, 2011;Grayson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Network modularity, a measure of the segregation between modules, is high during young adulthood and decreases across the latter life span (6,7). Other features of network reorganization accompany development (8), including a growing preference for interactions between hubs and nonhubs (9), and between regions separated by large physical distances (10).…”
mentioning
confidence: 99%